STUDI KASUS IMPLEMENTASI MODEL KOMUNIKASI PEMASARAN SOSTAC PADA CAFE 99% COFFEE & EATERY - Safarwati Putri, Meri; Wilamadina, Ratu (AT TARIIZ : Jurnal Ekonomi dan Bisnis Islam, 2025)
This study aims to determine the effect of education level and income level on interest in cash waqf with religiosity as a mediating variable. This study is quantitative in nature. The population consists of 90 Muslim civil servants. Data were collected using a questionnaire with a Likert scale, validity and reliability testing, and hypothesis testing using SmartPLS 4.0 software. The results of the study show that education level has a positive and significant effect on religiosity, income level has a positive and significant effect on religiosity, education level has no effect on interest in cash waqf, income level has a positive and significant effect on interest in cash waqf, and religiosity has a positive and significant effect on interest in cash waqf. Education level has a positive and significant effect on interest in monetary waqf with religiosity as a mediating variable, and income level has a positive and significant effect on interest in monetary waqf with religiosity as a mediating variable. Therefore, it is recommended that the government organize regular religious programs in the work environment of Muslim civil servants because religiosity has been proven to be a major factor in driving interest in monetary waqf.